Genetic differentiation and historical dynamics of the endemic species Rheum pumilum on the Qinghai-Tibetan Plateau inferred from phylogeography implications - Shuliang Liu; Jianxin Gao; Bo Xiao; Wenjie Guo; Qiushi Yu; Ailan Wang; Weiwei Li (BMC Plant Biology, 2025)
Abstract Background Rheum pumilum, an endemic species on the Qinghai-Tibetan Plateau (QTP), serves as an ideal material for investigating the phylogeography of alpine plants. This study employs chloroplast DNA fragments (trnL-F, trnS-G, and matK) to delve into how Rh. pumilum adapted to the extreme environmental changes on the QTP, during its evolutionary process through phylogenetic geographical analysis, revealing its population differentiation and historical dynamics. Results The examination of 39 haplotypes across 26 populations of Rh. pumilum reveals distinct regional distribution, reflecting a phylogeographic pattern resembling “alpine-island”. The total genetic diversity of Rh. pumilum is remarkably high (Ht = 0.910), with the majority of genetic variation primarily occurred among populations (84.5%) with limited gene flow, indicating geographic isolation influenced by diverse habitats of plateau. The geographic isolation model is further supported by various analytical methods, including AMOVA analysis, UPGMA dendrogram, PCoA, Structure analysis, and Mantel test. Micro-refugia for Rh. pumilum during the Quaternary ice ages are supported by haplotype network and genetic diversity analysis. The absence of a typical “star-shape” pattern in the overall haplotype network suggests that Rh. pumilum likely maintains a stable state without experiencing rapid expansion, which has been supported by mismatch distribution analysis. Ecological Niche Modeling (ENM) indicates sensitivity of Rh. pumilum to humidity, temperature and altitude, aligning with a historical distribution resembling a “displacement refugia” model during the Quaternary ice ages. The involvement of Rh. kialense and Rh. sublanceolatum in the origin and gene introgression of Rh. pumilum is suggested, possibly as maternal ancestors of closely related haplotypes. Haplotype divergence of Rh. pumilum approximately 11 million years ago, with notable divergence peaks observed during the late Miocene, as well as the Pliocene, Pleistocene and Holocene. Conclusion These findings suggest a correlation between genetic diversity, haplotype lineage divergence and key geological and climatic events, notably the uplift of the QTP, monsoon climate changes, and the climatic oscillations during the Quaternary ice ages. This study might provide valuable insights into the formation mechanisms of plant diversity on the QTP, crucial for biodiversity conservation and sustainable species development in extreme environments.